Deriving norms for learners in the disadvantaged schools of the peri-urban areas of the Eastern Cape: the case of the Vassiliou Mathematics Proficiency Test (VASSI) - Masango, Siphesihle Polkadot (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
This study builds on South African cross-cultural research which highlights the need for careful stratification of normative samples for quality of education and geographical location. The aim of the present study was to produce an expanded set of preliminary norms for learners in the disadvantaged schools of the peri-urban areas of the Eastern Cape, Grahamstown, on the Vassiliou Mathematics Foundation Phase Test (VASSI) and Vassiliou Mathematics Proficiency Test (VASSI), respectively. The test was administered to Grade 1-6 learners in four different schools all within Joza location, Grahamstown. For the learners' convenience the tests were translated into isiXhosa, the translations were provided together with the original English questions. Archival data collected by honours students was also incorporated in this study. The total number of participants was N=724 which was comprised of 147 grade 1s, 123 grade 2s, 117 grade 3s, 128 grade 4s, 113 grade 5s and 96 grade 6s. Norm-referenced criterion was used in analysing the data. The results of this study are in accordance with those purporting the low performance of disadvantaged learners on the school subject, mathematics. Stanines for the various grades (Grade 1 to 6) were calculated and are presented in the study. This study has demonstrated that although gender, language and other ethnic variables have an impact on mathematics performance, quality of education and socioeconomic status have a significant effect. Further research is needed on the effect of quality of education and socioeconomic status on learners in disadvantaged schools on this test in particular.
Keywords: VASSI Mathematics Proficiency Test; Mathematical ability -- Testing -- South Africa; Educational tests and measurements -- South Africa; Children with social disabilities -- Education -- South Africa; Children with social disabilities -- Education -- South Africa -- Makhanda -- Case studies